2023
DOI: 10.1108/bfj-02-2023-0132
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and new business models in agriculture: a structured literature review and future research agenda

Alberto Cavazza,
Francesca Dal Mas,
Paola Paoloni
et al.

Abstract: PurposeArtificial Intelligence (AI) is a growing technology impacting several business fields. The agricultural sector is facing several challenges, which may be supported by the use of such a new advanced technology. The aim of the paper is to map the state-of-the-art of AI applications in agriculture, their advantages, barriers, implications and the ability to lead to new business models, depicting a future research agenda.Design/methodology/approachA structured literature review has been conducted, and 37 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 75 publications
0
4
0
5
Order By: Relevance
“…Arthur Young notó la ausencia de registros contables de costos, que permitirían a los agricultores determinar el costo de los cultivos, los animales y los diferentes modos de cultivo. Sin embargo, en el siglo XVIII, la práctica de la contabilidad agrícola estaba en una etapa incipiente (Cavazza et al, 2023).…”
Section: El Desarrollo De Sistemas De Contabilidad De Costos En Las A...unclassified
See 1 more Smart Citation
“…Arthur Young notó la ausencia de registros contables de costos, que permitirían a los agricultores determinar el costo de los cultivos, los animales y los diferentes modos de cultivo. Sin embargo, en el siglo XVIII, la práctica de la contabilidad agrícola estaba en una etapa incipiente (Cavazza et al, 2023).…”
Section: El Desarrollo De Sistemas De Contabilidad De Costos En Las A...unclassified
“…Por tanto, la meticulosa recopilación y análisis de datos que demanda el sistema puede sobrepasar rápidamente la capacidad administrativa de dicho sector cuyas operaciones están intrínsecamente complicadas por la estacionalidad ambiental. Tal punto es corroborado por Cavazza et al (2023), quien subraya que las exigencias de dicha herramienta en términos de procesamiento de información pueden resultar abrumadoras para las empresas que ya enfrentan la incertidumbre de los ciclos naturales y de los mercados fluctuantes.…”
Section: Limitaciones Con La Implementación Y Usabilidad De Los Siste...unclassified
“…A remote monitoring system for their hives would be highly advantageous. However, these beekeepers frequently relocate their hives to remote or wooded areas, where both power supply limitations and signal strength can hinder data transmission [ 25 , 112 , 113 ]. Another critical issue is the beekeeper’s preparedness for the proficient use of these technological tools.…”
Section: Swot Analysis On the Application Of Pb Systemsmentioning
confidence: 99%
“…This is consistent with the observations in the current study, where AI-driven analytics have been identified as crucial for understanding consumer behavior and predicting market trends in real-time, thereby offering businesses a competitive edge. Cavazza et al (2023) explored AI's role in agriculture, presenting new business models that leverage AI for increased efficiency and sustainability. This research complements the findings of the present study by demonstrating AI's versatility and its capacity to drive innovation across different sectors, including agriculture.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…In agriculture, the practical applications of AI range from crop monitoring to predictive analysis of weather patterns, as discussed by Cavazza et al (2023). This not only improves crop yields but also contributes to sustainable farming practices, reflecting AI's potential to address global challenges such as food security and environmental sustainability.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%

Business Intelligence Transformation Through Ai and Data Analytics

Emmanuel Osamuyimen Eboigbe,
Oluwatoyin Ajoke Farayola,
Funmilola Olatundun Olatoye
et al. 2023
Eng. sci. technol. j.